Large eddy simulation of flow field in thermal vapor compressor - Ren, Xiaotong; Guo, Yali; Shen, Shengqiang; Zhang, Kun (Frontiers in Energy Research, 2022)
In the low-temperature multi-effect evaporation (LT-MEE) desalination plant, improving the performance of thermal vapor compressor (TVC) could reduce the energy loss, and increase the gained output ratio (GOR) and consequently improve the system economy efficiency. Implementing large eddy simulation (LES) as the numerical method, a 3-D computational fluid dynamics model of TVC is established to simulate the flow field under various conditions. The effects of motive steam pressure on the flow field, vortex core, turbulent viscosity and vortex iso-surface of the TVC are discussed, and the corresponding interior flow field distribution is obtained as well. Q criterion and normalized Q criterion are applied to visualize the vortex cores and vortex iso-surfaces. The distributions of vortexes in different scales are displayed, large-scale vortexes are mainly distributed in the exit area of the nozzle, the constant section of the mixing chamber and the diffuser. Additionally, the large-scale vortexes are primarily located along the axis in different morphology while the small-scale ones are randomly distributed near the wall.